Developing of Using Mineral Glass Media to Become a Number Funnel to Develop Cognitive Aspects of Early Age Children 5-6 Years - Helyawati, Elyn; Yusuf, Muhammad; Dea, Leli Fertiliana; Mahmudah, Masrurotul; Azizah, Isnaini Nur (Bulletin of Pedagogical Research, 2024)
The problem in this research is that used mineral water glasses turned into number funnels have not been utilized for cognitive learning in children aged 5-6 years, and the cognitive abilities of children aged 5-6 years are still underdeveloped. This study aims to develop used mineral water glasses into number funnels to enhance the cognitive aspects of children aged 5-6 years. This research uses R&D (Research and Development) with a 4D development model (Define, Design, Develop, Disseminate). The results of this study indicate that the number funnel media is deemed feasible by media and material experts. The effectiveness of using used mineral water glasses as number funnels to improve the cognitive aspects of children aged 5-6 years, after conducting research at TK Tunas Harapan Rejo Basuki using the number funnel media, proves that the cognitive abilities of early childhood can develop. Before using the number funnel media, out of 13 children, 7 were in the Not Yet Developed category, and 6 were in the Starting to Develop category, while none were in the Developing as Expected and Developing Very Well categories. After using the number funnel media, the cognitive abilities of children aged 5-6 years at TK Tunas Harapan Rejo Basuki were classified as Developing as Expected. The cognitive abilities of children in the Starting to Develop category were 5, in the Developing as Expected category were 6, and in the Developing Very Well category was 1, while there were no longer any in the Not Yet Developed category. Keyword: Learning Media, Developing Cognitive Aspects, Early Age Children